ANNOTATED BIBLIOGRAPHY OF BRATSK AND KRASNOIARSK HYDROELECTRIC PROJECTS IN CENTRAL SIBERIA, USSR - Sands, Anne W. (1966)
This annotated bibliography contains 352 references to books, monographs, pamphlets, and articles, largely from Soviet sources, on these 2 Siberian multiple-purpose projects being completed by Soviet constructors. The scope of the projects, size of the equipment being installed, and construction problems faced in an undeveloped taiga region with a severe climate make these projects of interest to American engineers. The USSR is understandably proud of its accomplishments and much has been written describing them. Soviet engineers have reported in detail the experience gained from the design, construction, and research problems and solutions as a basis for future construction of similar projects in Siberia. No effort has been made to evaluate the references, for the difference is usually one of attitude and not accuracy, and each contains some valuable or interesting information. The references are divided under these headings: General; Reservoirs and Dams; Powerplants; Turbines and Penstocks; Generators, Electrical Equipment, and Transmission Systems; Construction Materials and Equipment; and Welding and Metallurgy. They are relisted under headings of Bratsk and Krasnoiarsk by number, referring to the reference in the initial main category. Conversion nomographs, abbreviations and acronyms, and a list of Soviet technical periodicals are included under miscellaneous aids.